1982
DOI: 10.1172/jci110624
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Retention, and Biological Activity of Methotrexate Polyglutamates in Cultured Human Breast Cancer Cells

Abstract: A B S T R A C T To determine the pharmacologic importance of methotrexate (MTX) polyglutamates, we examined the formation, retention, and effect of these metabolites in cultured human breast cancer cells. Two cell lines converted the drug to y-polyglutamate derivatives in a dose-and timedependent reaction. After 24-h incubations with 2 zM MTX, polyglutamates of two to five amino acids in length accounted for 55.4% (51.9 nmol/g) of intracellular drug in the MCF-7 cells and 87.6% (62.4 nmol/ g) of drug in ZR-75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(61 citation statements)
references
References 21 publications
3
56
1
1
Order By: Relevance
“…However, after the 24-h incubation in drug-free media, MTX and MTX-Glu2 effluxed readily, and although the small quantities of longer polyglutamates were retained during efflux, their initial synthesis was insufficient to maintain drug in excess of the binding capacity. Closer study of individual polyglutamate metabolites confirmed that, as determined in prior experiments with breast cancer cell lines (13) and small-cell cell lines (17), drug retention correlates with glutamyl chain length. Thus, for all cell lines after a 24-h exposure to 1.0 1sM MTX, only 4-24% of parent drug present at the end of drug incubation remained after 24-h efflux, while 25% of MTX-Glu2, 70% of MTX-Glu3, 75% of MTX-Glu4, and 83% of MTX-Glu5 were retained.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…However, after the 24-h incubation in drug-free media, MTX and MTX-Glu2 effluxed readily, and although the small quantities of longer polyglutamates were retained during efflux, their initial synthesis was insufficient to maintain drug in excess of the binding capacity. Closer study of individual polyglutamate metabolites confirmed that, as determined in prior experiments with breast cancer cell lines (13) and small-cell cell lines (17), drug retention correlates with glutamyl chain length. Thus, for all cell lines after a 24-h exposure to 1.0 1sM MTX, only 4-24% of parent drug present at the end of drug incubation remained after 24-h efflux, while 25% of MTX-Glu2, 70% of MTX-Glu3, 75% of MTX-Glu4, and 83% of MTX-Glu5 were retained.…”
Section: Resultssupporting
confidence: 70%
“…In the absence of free drug, intracellular physiologic folates can compete for binding sites on DHFR, reversing enzyme inhibition (7)(8)(9). The transformation of MTX to polyglutamyl derivatives results in the formation of active metabolites of the drug that, when present in excess of the intracellular binding capacity, results in prolonged inhibition of DHFR (10)(11)(12)(13)(14)(15)(16)(17). In addition, MTX polyglutamates (MTX-PGs) may have additional sites of action as inhibitors of aminoimidazole carboxamide ribonucleotide transformylase (de novo purine synthesis) (18) and thymidylate synthase (TS) (19).…”
Section: Introductionmentioning
confidence: 99%
“…4. MTX, and folates in general, are metabolized intracellular to polyglutamate by folyl polyglutamate synthetase (34). MTX-polyglutamate is also preferentially retained in cells and has equal affinity with MTX for DHFR but dissociates at a slower rate and crosses cellular membranes less easily.…”
Section: Discussionmentioning
confidence: 99%
“…Their measurement in tissue culture cells has been achieved previously after incubation with radiolabelled compounds followed by extraction and HPLC separation (Jolivet et al, 1982;Sikora et al, 1988;Pizzomo et al, 1989;Jackman et al, 1991c;Gibson et al, 1993). Similar methodology has been used to measure the polyglutamated forms of methotrexate in isolated human leukaemic blast cells (Goker et al, 1993).…”
Section: Discussionmentioning
confidence: 99%